A Peer-Coaching–Based Professional Guidance Model for Islamic Education Teachers in Teacher Working Groups - Sarbini, Sarbini; Suhendi, Saca; Saadah, Susi; Fitriya, Erma; Aldi, Ujang; Darojat, Darojat; Haqq, Syauqi Arinal (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
This study aims to explore how peer coaching is implemented within Teacher Working Groups through a qualitative case study design. The participants involved were 10 Islamic education teachers, three administrators of the Islamic education teacher working group, and one Islamic education supervisor. Data were collected using in-depth interviews, observations, and document analysis to understand teachers’ real practices and experiences in conducting peer coaching. The findings show that peer coaching is implemented through regular collaborative meetings, blended learning sessions, and professional learning communities, which facilitate shared reflection and mutual feedback. The qualitative analysis indicates that peer coaching helps teachers improve lesson planning, diversify instructional strategies, and strengthen the use of formative assessments in PAI classrooms. It also fosters reflective thinking and enhances teachers’ adaptability to both the National Curriculum and the Merdeka Curriculum. However, several challenges were identified, including inconsistent implementation, limited time allocation, and varying levels of teachers' readiness to engage in critical reflection. The study concludes that optimized peer coaching requires stronger institutional support and more structured, continuous professional development to maximize its contribution to improving teaching practices in Islamic Education.